A fuzzy ontology: on the relevance of ecocentrism in marine environmental ethics - von Negenborn, Colin (WMU journal of maritime affairs, 2022)
Governing human interaction in the maritime space implicitly rests on the ascription of value to this space. Environmental ethics helps to disentangle the many concepts of value that may come in conflict. As a particularly contested concept, ecocentrism assigns value not just at the atomistic level, but also at the holistic one. It has, however, been subject to criticism, thus challenging the validity of recent approaches to ocean management implicitly resting on ecocentric grounds. This paper provides a new justification for ecocentrism in the marine realm. Instead of relying on notions of community or teleonomy in nature, this paper builds on its ontology. It considers “the Area” beyond national jurisdiction and its declaration as “common heritage.” While a shared understanding of this concept is necessary to put it to practice in the intergovernmental sphere, the paper argues that any characterization of its ontology is subject to fuzziness. In the light of disagreement, fluctuation, and uncertainty on the atomistic level, a holistic perspective on the Area is necessary. Ecocentrism thus allows to overcome the conceptual hindrances and facilitates the implementation of a genuinely common heritage.